Svetozar Marković and the main trends of European socialism (1840–1890) - Mandić, Stefan (Sociološki pregled, 2026)
Different intellectual traditions and periods have interpreted Svetozar Marković’s work in completely different ways. According to the majority of authors, Marković ranks among social utopians whose thought was crucially influenced by Russian populism. Certain theoreticians look at him as a founder of particular Balkan socialism, while others consider his work close to Marxism or even anarchism. Furthermore, in the intellectual public there is no consensus about whether Marković’s thought is rational and progressive, or irrational and anti-modernist. While most authors believe that Marković was a progressive thinker, some of them, particularly those from the circle of modern Serbian liberals, believe that his thought is anti-modernist. The main goal of this paper is to establish what type of Socialism was “preached” by Svetozar Marković and whether he can be ranked among progressive intellectual forces. That is why Marković’s worldview has been compared with the theoretical postulates of Marx, Chernyshevsky, Bakunin and Proudhon, the most significant socialists in the period 1840-1890. The main conclusion of this paper is that Svetozar Marković was a progressive thinker and that he should be considered a libertarian multilinear Marxist with revisionist tendencies or a syntheticist of Marxism and Russian populism.
Keywords: Svetozar Marković (1846–1875); Karl Marx (1818–1883); Nikolai Chernyshevsky (1828–1889); Mikhail Bakunin (1814–1876); Pierre-Joseph Proudhon (1809–1865)